Interchromosomal communication coordinates intrinsically stochastic expression between alleles - Johnston, Robert J. (2014)
Sensory systems use stochastic mechanisms to diversify neuronal subtypes. In the Drosophila eye, stochastic expression of the PAS-bHLH transcription factor Spineless (Ss) determines a random binary subtype choice in R7 photoreceptors. Here, we show that a stochastic, cell-autonomous decision to express ss is made intrinsically by each ss locus. Stochastic on or off expression of each ss allele is determined by combinatorial inputs from one enhancer and two silencers acting at long range. However, the two ss alleles also average their frequency of expression through upregulatory and downregulatory interallelic cross-talk. This inter- or intra-chromosomal long-range regulation does not require endogenous ss chromosomal positioning or pairing. Therefore, although individual ss alleles make independent stochastic choices, interchromosomal communication coordinates expression state between alleles, ensuring that they are both expressed in the same random subset of R7s.